Microwave-intensified esterification of high-free fatty acid feedstock into biodiesel using waste chicken eggshells as a heterogeneous catalyst - Juliati Br Tarigan; Anzelina F. Barus; Nabilah T. Simamora; Ribka S. Tarigan; Sabarmin Perangin-angin; Junedi Ginting; Eko K. Sitepu; Y.H. Taufiq-Yap (Case Studies in Chemical and Environmental Engineering)
The efficacy of waste chicken eggshells as a heterogeneous catalyst is investigated for biodiesel production from high-free fatty acid feedstock under microwave irradiation. The calcined waste chicken eggshells were identified using Thermogravimetric Analysis (TGA), X-ray Diffraction (XRD), X-ray Fluorescence (XRF) and Scanning Electron Microscope (SEM) equipped with Energy Dispersive X-ray (EDX). The effect of esterification conditions such as catalyst weight, molar ratio of oleic acid to methanol, reaction time and microwave power were determined on biodiesel conversion and yield. The highest conversion and yield of 92.04 ± 0.8 % and 78.75 ± 1.8 %, respectively, were achieved under the reaction condition of molar ratio of 1:15, catalyst weight of 6 wt%, reaction time of 20 minutes and microwave power of 60 %. The catalytic stability of calcined waste chicken eggshells revealed that the weight of CaO was decreased after the first cycle. However, the biodiesel conversion was above 80 % after five times usage.